Policy Implementation of Regional Relief Response (RR-RD) Call Center - Legi, Christian; Masengi, Evi E.; Wawointana, Thelma (JR Education, 2022)
response regional reaction (RR-RD) policy at the Minahasa Regency Communication and Information Service and to find out the obstacles faced by the Communication and Informatics Agency in implementing this policy. The research method used is a qualitative method, namely answering a problem in depth in the context of the time and situation in question, in accordance with the objective conditions in the field and the type of research used is descriptive qualitative, namely describing the condition of the object in the present qualitatively the data obtained from the research. The data sources used are primary data sources and secondary data sources with 5 informants. Data collection techniques using the method of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of the study showed that (a) communication, indicating that communication was running, seen from the socialization delivered by the local government to the community and village/ward governments regarding the application program reaksi response relief regional (RR-RD) call center, but it was not optimal because the socialization was not yet evenly distributed throughout all areas in Minahasa. (b) resources, indicating that it is good enough in terms of human resources and the availability of supporting facilities in managing this application program, (c) disposition, indicating that the Regional Government has carried out its duties properly seen from the way it follows up on incoming complaints and the socialization delivered to the community and the village/kelurahan government of the Minahasa regency, (d) the bureaucratic structure or bureaucratic structure, shows that the implementation of the application program reaksi response relief regional (RR-RD) call center is clear and in accordance with the applicable SOPs.